Gelatinase activity imaged by activatable cell-penetrating peptides in cell-based and in vivo models of stroke. Issue 1 (January 2017) - Chen, Shanyan; Cui, Jiankun; Jiang, Tao; Olson, Emilia S; Cai, Quan-Yu; Yang, Ming; Wu, Wei; Guthrie, James M; Robertson, JD; Lipton, Stuart A; Ma, Lixin; Tsien, Roger Y; et al.
Matrix metalloproteinases (MMPs), particularly gelatinases (MMP-2/-9), are involved in neurovascular impairment after stroke. Detection of gelatinase activity in vivo can provide insight into blood–brain barrier disruption, hemorrhage, and nerve cell injury or death. We applied gelatinase-activatable cell-penetrating peptides (ACPP) with a cleavablel -amino acid linker to examine gelatinase activity in primary neurons in culture and ischemic mouse brain in vivo . We found uptake of Cy5-conjugated ACPP (ACPP-Cy5) due to gelatinase activation both in cultured neurons exposed to n -methyl-d -aspartate and in mice after cerebral ischemia. Fluorescence intensity was significantly reduced when cells or mice were treated with MMP inhibitors or when a cleavage-resistant ACPP-Cy5 was substituted. We also applied an ACPP dendrimer (ACPPD) conjugated with multiple Cy5 and/or gadolinium moieties for fluorescence and magnetic resonance imaging (MRI) in intact animals. Fluorescence analysis showed that ACPPD was detected in sub-femtomole range in ischemic tissues. Moreover, MRI and inductively coupled plasma mass spectrometry revealed that ACPPD produced quantitative measures of gelatinase activity in the ischemic region. The resulting spatial pattern of gelatinase activity and neurodegeneration were very similar. We conclude that ACPPs are capable of tracing spatiotemporal gelatinase activity in vivo, and will therefore be useful in elucidating mechanisms of gelatinase-mediated neurodegeneration after stroke.